At Westonci.ca, we provide reliable answers to your questions from a community of experts. Start exploring today! Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

the steps to solve the equations 7 + 2(3x +4) = 3

Sagot :

[tex]\begin{gathered} 7+2(3x+4)=3 \\ \end{gathered}[/tex]

we subtract 7 from the two sides

[tex]\begin{gathered} 2(3x+4)=3-7 \\ 2(3x+4)=-4 \end{gathered}[/tex]

we divide 2 from the two sides

[tex]\begin{gathered} 3x+4=\frac{-4}{2} \\ 3x+4=-2 \end{gathered}[/tex]

we subtract 4 from the two sides

[tex]\begin{gathered} 3x=-2-4 \\ 3x=-6 \end{gathered}[/tex]

we divide 3 from the two sides

[tex]\begin{gathered} x=-\frac{6}{3} \\ x=-2 \end{gathered}[/tex]

we can check

[tex]\begin{gathered} 7+2(3(-2)+4)=3 \\ 7+2(-6+4)=3 \\ 7+2(-2)=3 \\ 7+(-4)=3 \\ 7-4=3 \\ 3=3 \end{gathered}[/tex]